Evaluation of dendritic cell-targeting T7 phages as a vehicle to deliver avian influenza virus H5 DNA vaccine in SPF chickens - Xu, Hai; Li, Ling; Li, Ruiting; Guo, Zijie; Lin, Mengzhou; Lu, Yu; Hou, Jibo; Govinden, Roshini; Deng, Bihua; Chenia, Hafizah Y. (Frontiers in Immunology, 2022)
There is a growing demand for effective technologies for the delivery of antigen to antigen-presenting cells (APCs) and their immune-activation for the success of DNA vaccines. Therefore, dendritic cell (DC)-targeting T7 phages were used as a vehicle to deliver DNA vaccine. In this study, a eukaryotic expression plasmid pEGFP-C1-HA2-AS containing the HA2 gene derived from the avian H5N1 virus and an anchor sequence (AS) gene required for the T7 phage packaging process was developed. To verify the feasibility of phage delivery, the plasmid encapsulated in DC-targeting phage capsid through the recognition of AS was evaluated both in vitro and in vivo. The pEGFP-C1-HA2-AS plasmid could evade digestion by DNase Ⅰ by becoming encapsulated into the phage particles and efficiently expressed the HA2 antigen in DCs with the benefit of DC-targeting phages. For chickens immunized with the DC-targeting phage 74 delivered DNA vaccine, the levels of IgY and IgA antibodies, the concentration of IFN-γ and IL-12 cytokines in serum, the proliferation of lymphocytes, and the percentage of CD4+/CD8+ T lymphocytes isolated from peripheral blood were significantly higher than chickens which were immunized with DNA vaccine that was delivered by non-DC-targeting phage or placebo (p＜0.05). Phage 74 delivered one-fiftieth the amount of pEGFP-C1-HA2-AS plasmid compared to Lipofectin, however, a comparable humoral and cellular immune response was achieved. Although, the HA2 DNA vaccine delivered by the DC-targeting phage induced enhanced immune responses, the protection rate of virus challenge was not evaluated. This study provides a strategy for development of a novel avian influenza DNA vaccine and demonstrates the potential of DC-targeting phage as a DNA vaccine delivery vehicle.